Transformative medical education: must community-based traineeship experiences be part of the curriculum? A qualitative study - Julie Massé; Sophie Dupéré; Élisabeth Martin; Martine C. Lévesque (BMC, 2020)
Abstract Background There are shortcomings in medical practitioners' capacity to adapt to the particular needs of people experiencing circumstances of social vulnerability. Clinical traineeships create opportunities for the acquisition of knowledge, competencies, attitudes, and behaviors. However, some authors question the learnings to be made through classical clinical training pathways. This article explores the learnings gained from a traineeship experience within a community-based clinical setting intended for patients experiencing social vulnerability and operating under an alternative paradigm of care. To our knowledge, there is little research intended to identify and understand what medical trainees gain from their experience in such contexts. Methods This exploratory qualitative study is based on twelve interviews with practicing physicians who completed a traineeship at La Maison Bleue (Montreal, Canada) and three interviews conducted with key informants involved in traineeship management. Based on Mezirow's theory of transformational learning, data were analyzed according to L'Écuyer's principles of qualitative content analysis. NVivo software was used. Results The main learnings gained through the traineeship are related to (1) greater awareness of beliefs, assumptions and biases through prejudice deconstruction, cultural humility and critical reflection on own limitations, power and privileges; (2) the development of critical perspectives regarding the health care system; (3) a renewed vision of medical practice involving a less stigmatizing approach, advocacy, empowerment, interdisciplinarity and intersectorality; and (4) strengthened professional identity and future practice orientation including confirmation of interest for community-based practice, the identification of criteria for choosing a future practice setting, and commitment to becoming an actor of social change. Certain characteristics of the setting, the patients and the learner's individual profile are shown to be factors that promote these learnings. Conclusions This article highlights how a traineeship experience within a clinical setting intended for a clientele experiencing circumstances of social vulnerability and operating under an alternative paradigm presents an opportunity for transformative learning and health practice transformation toward renewed values of health equity and social justice. Our findings suggest medical traineeships in community-based clinical settings are a promising lead to foster the development of fundamental learnings that are conducive to acceptable and equitable care for people experiencing social vulnerability.